Genome-wide identification of potato Trihelix gene family and its response to different abiotic stresses - Hongyu Yang; Yan Wang; Taotao Liu; Wenxia Yao; Xiangjun Fan; Bin Yu; Guiying Shi (BMC Plant Biology)
Abstract The Trihelix transcription factor family, characterized by its unique triple-helix structure (helix-loop-helix-loop-helix), plays a significant role in plant growth, development, and responses to various abiotic stresses. Potato (Solanum tuberosum L.), as a globally important food crop, experiences significant impacts on its growth and yield due to abiotic stresses such as drought, low temperature, and salt stress. Although the functions of Trihelix transcription factors have been extensively studied in various plants, systematic analysis in potatoes remains relatively scarce. This study aims to comprehensively identify the Trihelix gene family in potatoes through bioinformatics methods and analyze their expression patterns under abiotic stresses to reveal the potential functions of this gene family in potato growth, development, and stress responses. Through genome database searches and BLAST comparisons, 35 StTrihelix genes were identified in potatoes, and phylogenetic, gene structure, functional motif, and cis-acting element analyses were conducted. The expression patterns of these genes in different tissues and under low-temperature and drought stresses were analyzed using qRT-PCR technology. Additionally, the nuclear localization of StTrihelix30 was verified through subcellular localization experiments. The results indicate that the 35 StTrihelix genes are unevenly distributed across 12 chromosomes and can be classified into five subfamilies: GT-1, GT-2, GTγ, SH4, and SIP1. Gene structure and functional motif analyses revealed high conservation within the same subfamily. Cis-acting element analysis showed that these genes are closely related to hormone responses, stress responses, and growth and development processes. Tissue expression analysis showed that StTrihelix4 is highly expressed in stamens, while StTrihelix13 is highly expressed in roots. qRT-PCR results indicated that most StTrihelix genes are significantly upregulated under low-temperature and drought stresses. This study systematically identified the Trihelix gene family in potatoes and revealed its important role in abiotic stress responses. It provides new insights into the functions of the Trihelix transcription factor family in potato growth, development, and stress adaptation, offering theoretical references for stress-resistant potato breeding.